2010
DOI: 10.1002/hyp.7755
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the spatial distribution of imperviousness on the hydrologic response of an urbanizing basin

Abstract: Abstract:An event-based model is used to investigate the impact of the spatial distribution of imperviousness on the hydrologic response of a basin characterized by an urban land use. The impact of the spatial distribution of imperviousness is investigated by accounting for its location within the basin when estimating the generated runoff and the hydrologic response. The event model accounts for infiltration and saturation excess; the excess runoff is routed to the outlet using a geomorphologic unit hydrograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0
5

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(66 citation statements)
references
References 49 publications
2
59
0
5
Order By: Relevance
“…interruption of public services and economic activities), especially in the urbanized areas around the world (e.g. Ramos et al 2005;Mejia and Moglen 2010;Smith et al 2012;Wright et al 2012). PFF is a rapid flood caused by heavy rain and can be distinguished from a regular pluvial flood by a short timescale, generally less than six hours.…”
Section: Introductionmentioning
confidence: 99%
“…interruption of public services and economic activities), especially in the urbanized areas around the world (e.g. Ramos et al 2005;Mejia and Moglen 2010;Smith et al 2012;Wright et al 2012). PFF is a rapid flood caused by heavy rain and can be distinguished from a regular pluvial flood by a short timescale, generally less than six hours.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies found that the composition of the impervious surface (the impervious surface area) reduced the total infiltration of water into the surface and, thereby, increased the surface runoff and peak discharge, which ultimately raised the associated risk of urban flooding [27,28]. In addition, several studies showed that the spatial configuration of the impervious surface influenced surface runoff and the potential urban flood risk, as well [27,29,30]. However, most previous studies primarily highlighted the importance of the location of the impervious surface (e.g., upstream, midstream or downstream) in an urban watershed or catchment to define the influence of the spatial configuration of the impervious surface.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of urbanization on land processes can be an important control, and later, the research focused on the implementation of urban planning technologies, such as LID (Low Impact Development) in North America [24,25], for which, equivalent terms such as sustainable urban drainage systems (SUDS) in the United Kingdom, water-sensitive urban design (WSUD) in Australia [26] and the Low Impact Urban Development Design (LIUDD) [27], is an alternative approach to stormwater management and avoid negative effects of conventional urban land redevelopment by using the catchment context as the design framework and encouraging the minimization and the clustering of urbanization areas to maximize surface permeability. A catchment-based structure planning approach needs to involve all professional sectors and a nested hierarchy of units for design and management [28], and should begin whilst a basin is still in its natural state [29][30][31].…”
Section: Introductionmentioning
confidence: 99%